Semiclassical solutions for Choquard equations with Berestycki–Lions type conditions. (November 2019) - Zhang, Jing; Wu, Qingfang; Qin, Dongdong
Abstract: This paper is concerned with existence of multiple semiclassical states for a class of Choquard equation. Under the classic Berestycki–Lions type assumptions assumed on the nonlinearity, we obtain multiplicity of semiclassical solutions for the equation by using a method of penalization argument. We study further the concentration phenomena of such solutions and show that they converge to the least energy solutions of the associated limit problem as the parameter ε goes to 0.